Tradição, memória e identidade: as narrativas indígenas potiguara (re)contadas nas aldeias Jacaré de César e Três Rios - Barbosa, Milena Veríssimo (2021)
Narrating events that occur on a daily basis, telling fabulous stories and great deeds, as well as describing supernatural beings and their actions, are tasks inherent to subjects in different societies. The Potiguara indigenous people, through the elders, also use storytelling to communicate their culture, identity and traditions. However, these narratives are still shared only through orality, without the written record of narratives that deal with the origins of families, how the process ofsettlement took place within the villages, as well asthe supernatural stories surrounding the daily lives of indigenous relatives. In this context, this research sought to bring together, through the collection of reports among the elders, a set of narratives present in the collective imagination of the Potiguara people located on the North Coast of Paraíba, in order to register, through writing, narratives of the oral tradition that permeate the indigenous daily life of this region. Authors such as Ong (1998), Cascudo (2007), Munduruku (2009), Le Goff (1990), Halbwachs (1993), Moonem and Maia (2008) Cardoso and Guimarães (2012), Benjamin (1994), among others, supported this research. From a methodological point of view, a field research was carried out, using semi-structured interviews as a data collection instrument. The collected reports were analyzed from three perspectives: oral tradition, memory and identity. Among the main contributions of this dissertation, there is the collection and written record of the narratives told by the Potiguara elders, which are part of the collective memory of this people around their ancestors,supernatural beings and the territorial and cultural struggles that collaborate in the construction and strengthening the identity of new generations.